Players' Value Structure in Digital Games. (January 2017) - Lin, Yu-Ling; Lin, Hong-Wen; Yang, Ya-Ting
The rapid advancement of digital games has not only brought entertainment to consumers but also triggered gamers' motivation to play. This study attempts to examine the structure of "attribute–consequence–value" chains of digital games based on the theoretical framework of means-end chains (MECs) and soft laddering interview technique. Results of the study reveal that players pay attention to game attributes including connection system, popular, graphic design, and diverse game genres. From these attributes, players expect consequences such as improve interactivity, cultivate logic and reflex, gain authentic experience, enhance pleasure of senses, and utilize imagination in pursuit of terminal values such as fun and enjoyment of life, sense of accomplishment, warm relationship with others and excitement . The study also covers the differences in the chains for different platforms of digital games and players of different gender. The results showed that different groups have different needs.